2013
DOI: 10.1177/0148607113487216
|View full text |Cite
|
Sign up to set email alerts
|

A.S.P.E.N. Clinical Guidelines

Abstract: (1) What maternal risk factors predispose the neonate to metabolic bone disease? (2) What is the optimal type of feeding to promote neonatal bone health? (3) When and how should vitamin D supplements be administered? (4) Does parenteral nutrition (PN) predispose a neonate to metabolic bone disease, and if so, are there PN formulation recommendations to minimize this risk?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 65 publications
0
31
0
2
Order By: Relevance
“…The last 3 months of pregnancy are important because the fetus acquires 80% of calcium and phosphorus reserves between 25 and 40 weeks of gestation. [ 8 , 9 ] In this period, the mean deposition rates of calcium and phosphorus are 100 to 120 and 50 to 65 mg/kg/day, which provide the newborn with 20 and 10 g of calcium and phosphorus reserves. If preterm birth occurs in this period, the newborn will partially or completely miss the optimal stage of acquiring calcium and phosphorus reserves.…”
Section: Discussionmentioning
confidence: 99%
“…The last 3 months of pregnancy are important because the fetus acquires 80% of calcium and phosphorus reserves between 25 and 40 weeks of gestation. [ 8 , 9 ] In this period, the mean deposition rates of calcium and phosphorus are 100 to 120 and 50 to 65 mg/kg/day, which provide the newborn with 20 and 10 g of calcium and phosphorus reserves. If preterm birth occurs in this period, the newborn will partially or completely miss the optimal stage of acquiring calcium and phosphorus reserves.…”
Section: Discussionmentioning
confidence: 99%
“…This is often an individualized approach based on clinical experience as there is limited research with which to guide providers. Enhanced formula continued until term benefits growth and bone health in otherwise well former preterm infants, but the data is insufficient for those with more comorbidities [34] . Transitional formula or breast milk fortification may be empirically provided until 40–52 weeks post-conceptional age [33] or up to 6 months if ongoing concerns for growth exist [35] .…”
Section: Post-dischargementioning
confidence: 99%
“… 93 The prevalence of atopy, allergic rhinitis, and asthma at age 31 y was higher in people who, as infants, had been supplemented regularly with approximately 2000 IU of vitamin D per day—a dose significantly higher than that usually recommended for infants. 94 Those associations (other than for asthma) remained significant after adjustment for potential confounders, but data for serum 25(OH)D concentrations were unavailable. Another study, reported an almost twofold increase in susceptibility to asthma and food hypersensitivity after supplementation with vitamin D (400 IU/d) and vitamin A (1000 IU) for the first year of life.…”
Section: Resultsmentioning
confidence: 99%